2022
DOI: 10.52965/001c.35482
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associated Risk Factors of Irritable Bowel Syndrome Among Female Secondary School students in Ar Rass City, Qassim Region

Abstract: Background Irritable bowel syndrome (IBS) is a common chronic gastrointestinal condition associated with many modifiable and non-modifiable risk factors. Objectives To determine the prevalence of IBS and the associated risk factors among female secondary school students in Ar Rass city, Qassim region, Saudi Arabia. Methods A cross-sectional study was conducted from June to August 2021 among female students attending government secondary schools at Ar Rass city, Qassim region. Two schools were selected by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…Experiencing abdominal pain was significantly associated with IBS diagnosis, confirming previous findings. This study corroborates previous research by [4,14], suggesting a potential link between frequent abdominal pain and IBS. Individuals reporting abdominal pain had approximately 2.54 times higher odds of receiving an IBS diagnosis compared to those without such symptoms, with a confidence level of 99%.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Experiencing abdominal pain was significantly associated with IBS diagnosis, confirming previous findings. This study corroborates previous research by [4,14], suggesting a potential link between frequent abdominal pain and IBS. Individuals reporting abdominal pain had approximately 2.54 times higher odds of receiving an IBS diagnosis compared to those without such symptoms, with a confidence level of 99%.…”
Section: Discussionsupporting
confidence: 92%
“…The study linked alcohol consumption and depression as the primary factors associated with IBS [3]. IBS is recognized as one of the most prevalent chronic gastrointestinal disorders, distinguished by frequent abdominal pain and alterations in stool appearance or frequency [4]. Symptoms can vary greatly among individuals, with some experiencing severe symptoms and others only mild to moderate ones.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of IBS found in the current study is similar to that found in a recent study of female secondary school students in Ar Rass, Qassim region, Saudi Arabia. According to the study, the prevalence was 21.4% [ 23 ]. This prevalence, however, is higher than that reported in a Korean study of adolescents, which found it to be 10.7% [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, most studies reported female predominance [ 15 , 25 , 27 ]. The associated factors among these studies were poor diet, physical inactivity, depression, low quality of life, family history, and smoking [ 16 , 21 , 30 , 32 , 40 , 41 ]. Only four studies with 1,218 participants were based on healthcare professionals of both genders, with a pooled prevalence of 18.3%.…”
Section: Reviewmentioning
confidence: 99%